Intergovernmental Relations and Federal Roads Infrastructure Development in Nigeria: A Study of Delta and Edo States (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
The study examined intergovernmental relations and federal roads infrastructure development in Nigeria Delta and Edo States a case study. The study adopted Structural-Functionalism Theory. The study employed the descriptive research design. The study evaluates the independence or correlation between categorical variables represented in the Likert scale responses. The study used both qualitative and quantitative sources. The study revealed that many of the respondents agreed that IGR has a positive impact on governance and road infrastructure. The study revealed that political rivalry as another challenge; 51.2% of the respondents strongly agreed and 40% agreed that the conflicts between federal and state governments hinder infrastructure development. The study recommended that both the federal and state governments need to guarantee adequate funding for road projects, along with measures in place to promote transparency and accountability in order to prevent corruption and inefficiencies, among others.